Report on a Large Hoard of Anglo-Saxon Pennies, in Silver, Found in the Island of Islay (Proceedings of the Society of Antiquaries of Scotland, 1852)
W.H. Scott's report on a hoard of pennies found on a farm on the Isle of Islay. A very small portion of the hoard was recovered by the Scottish Exchequer, which Mr. Scott was privileged to catalogue. Among the coins were pennies belonging to the reigns of Aethelstan, Eadmund, Eadred, Eadwig, and Eadgar, as well as a St. Peter's penny, a Cufic dirham, and some irregular bars of silver. Scott gives a detailed description of the coins.